Multicenter Validation of the cppB Gene as a PCR Target for Detection of Neisseria gonorrhoeae - Bruisten, S. M. (American Society for Microbiology, 2004)
The cppB gene is often used as a target for detection of Neisseria gonorrhoeae by PCR. Using a coded panel of 500 DNA samples, we determined that the cppB gene is missing in 5.8% of N. gonorrhoeae strains, and therefore we consider the cppB gene to be an unsuitable target.